2021
DOI: 10.1136/fmch-2021-001034
|View full text |Cite
|
Sign up to set email alerts
|

Impact evaluation of immunisation service integration to nutrition programmes and paediatric outpatient departments of primary healthcare centres in Rumbek East and Rumbek Centre counties of South Sudan

Abstract: ObjectiveTo evaluate the impact of immunisation service integration to nutrition programmes and under 5-year-old paediatric outpatient departments of primary healthcare centres in Rumbek East and Rumbek Centre counties of South Sudan.DesignRetrospective intervention study.SettingThree primary healthcare centres in Rumbek East county and three primary healthcare centres in Rumbek Centre county of Lakes state in South Sudan.ParticipantWe extracted the data for the uptake of pentavalent vaccine (first, second and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Six studies considered system adaptation through service integration – four from sub-Saharan Africa and two from South Asia (Afghanistan and Pakistan). Two studies evaluated the impact of Mobile Health Teams (MHTs) offering integrated PHC including vaccination delivery in Afghanistan and Nigeria (54,55); two looked at integration between nutrition and routine immunisation services in South Sudan (56,57); and the final two studies considered integration of routine immunisation with polio outreach activities in Nigeria and Pakistan (58,59). All bar one were observational studies; the final study was a high-quality cluster RCT from Pakistan (59).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies considered system adaptation through service integration – four from sub-Saharan Africa and two from South Asia (Afghanistan and Pakistan). Two studies evaluated the impact of Mobile Health Teams (MHTs) offering integrated PHC including vaccination delivery in Afghanistan and Nigeria (54,55); two looked at integration between nutrition and routine immunisation services in South Sudan (56,57); and the final two studies considered integration of routine immunisation with polio outreach activities in Nigeria and Pakistan (58,59). All bar one were observational studies; the final study was a high-quality cluster RCT from Pakistan (59).…”
Section: Resultsmentioning
confidence: 99%
“…This study observed that health facilities frequently conducting routine (static) immunization services on a daily basis were influential in reducing the amount of children off track with immunization. Policy on immunization in South Sudan advises the implementation of routine immunization outreach across communities outside the 5 km radius of a health facility [ 1 , 36 , 37 ]. Considering the need for improvement of immunization success in countries like South Sudan, continuous vaccine availability and punctuality of EPI vaccinators at health facilities, creation and sustainability of more outreach posts with regular supplementary immunisation activities in hard-to-reach areas could translate into higher vaccine uptake.…”
Section: Discussionmentioning
confidence: 99%
“…According to a unicef report, a ‘one-size-fits-all’ approach in this changing world is no longer appropriate [ 38 ]. Nevertheless, analysis of data available from DHIS2 have shown more vaccination still takes place during outreaches activities for most counties in south Sudan [ 1 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations